Pengelolaan Pembelajaran Al-Qur'an Melalui Metode Demonstrasi untuk Mengembangkan Afektif Peserta Didik pada SMP Perjuangan dan Informatika Terpadu Depok - Zaenuri, Zaenuri (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2023)
This research aims to find out how Al-Qur'an learning is managed in developing students' affectivity using the demonstration method at SMP Perjuangan and Integrated Informatics Depok, West Java. This research uses descriptive qualitative research methods and data collection tools through interviews, observation and document study. Data analysis uses reduction, data presentation and verification. The sample or what is called the main informant in this research are Al-Qur'an teachers. The results of this research show that learning management in developing students' affectivity using the demonstration method is as follows: 1) Learning planning for the Al-Qur'an program is planned for daily, weekly and semester activities, where each meeting will be filled with tahsin and tahfizh material. In accordance with the learning targets, the target for learning the Al-Qur'an is 2 juz for 3 years, where in the first year and second year it is used to memorize and in the third year to repeat memorization. 2) organizing tahfidz is dividing a group of students into three parts. In each Al-Qur'an group there is one Qur'an teacher and students. grouped based on students' ability to read when they first enter school or during the entrance exam for new students. 3) Implementation of learning activities begins with an opening, greeting, prayer and providing motivation before entering the core material that you want to convey. The opening activities include maintaining etiquette when studying, preparing learning tools, praying, taking attendance, providing motivation and notifying the learning targets you want to study at each meeting. 4) Evaluation in daily teaching and learning activities is only a memorization deposit at the end of the session, apart from that there is a mid-semester exam and final semester exam in the form of a practical exam in reading the Al-Qur'an and a memorization exam in the form of connecting verses. 5) 5) Students' affective development is carried out by providing demonstrations in accordance with the learning material. Some teachers have done it, but some teachers still have not implemented this method.